2020
DOI: 10.3390/pathogens9070535
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Interferon-Gamma Polymorphisms as a Risk Factor in Feline Infectious Peritonitis Development in Non-Pedigree Cats—A Large Cohort Study

Abstract: Feline infectious peritonitis (FIP) is a common infectious cause of death in cats, with heritable host factors associated with altered risk of disease. To assess the role of feline interferon-gamma gene (fIFNG) variants in this risk, the allele frequencies of two single nucleotide polymorphisms (SNPs) (g.401 and g.408) were determined for non-pedigree cats either with confirmed FIP (n = 59) or from the general population (cats enrolled in a large lifetime longitudinal study; n = 264). DNA was extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In the first place, our marker set could be non-informative for revealing such a substructure. Although the breeds involved were reported as more resistant or more susceptible to FIP in the literature, literary data on associations of various markers with clinical FIP are not fully consistent [ 3 , 14 , 15 , 16 ], and there is no experimental evidence on associations of the markers with clinical phenotypes. Besides this explanation, it is possible that even an informative marker set would produce the same data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first place, our marker set could be non-informative for revealing such a substructure. Although the breeds involved were reported as more resistant or more susceptible to FIP in the literature, literary data on associations of various markers with clinical FIP are not fully consistent [ 3 , 14 , 15 , 16 ], and there is no experimental evidence on associations of the markers with clinical phenotypes. Besides this explanation, it is possible that even an informative marker set would produce the same data.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical associations of candidate immune response (IR) genes, such as interferon-gamma and tumor necrosis factor alpha coding genes, with individual variability in clinical FIP status were analyzed with sometimes controversial results [ 3 , 14 , 15 , 16 ]. Two GWAS studies were performed, resulting in a definition of candidate regions associated with FIP [ 10 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some ‘FIP-resistant’ and ‘FIP-susceptible’ alleles were suggested, and a subsequent study found an increased frequency of documented feline IFN-γ SNPs in pedigree cats, but small numbers limited statistical analysis [ 199 ]. A larger study [ 200 ] published on the prevalence of feline IFN-γ SNPs in non-pedigree cats did find a statistical association between the presence or absence of FIP and genotype; however, the strength of this association (presence of the ‘protective’ genotype in 16% of the cats with FIP and its absence in 66% of the cats without FIP) limits its use in individual cats or to guide breeding. Another study found associations between FIP and SNPs in the TNF-α and the dendritic cell-specific intercellular adhesion molecule-grabbing non-integrin (DC-SIGN) genes [ 201 ], although no such associations were found in a subsequent study [ 199 ].…”
Section: Immunitymentioning
confidence: 99%
“…An inherited susceptibility to FIP has been shown in pedigree cats [24] but attempts to selectively breed resistant cats have failed [25]. Variants of the feline interferon-gamma gene (fIFNG) are thought to be associated with the risk of disease, but a study investigating the clinical use of this association to select cats for breeding could not show reliable results [26]. Another study evaluated the use of a novel feline infectious peritonitis virus (FIPV)-targeted RT-PCR to distinguish the avirulent pathotype from the virulent mutant, but the differentiation was not accurate [27].…”
Section: Introductionmentioning
confidence: 99%